2022
DOI: 10.1186/s12967-021-03211-8
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 promotes cardiac fibrosis in heart failure through increased recruitment of EZH2 to the Smad7 promoter region

Abstract: Cardiac fibrosis, a well-known major pathological process that ultimately leads to heart failure, has attracted increasing attention and focus in recent years. A large amount of research indicates that long noncoding RNAs (lncRNAs) play an important role in cardiac fibrosis, but little is known about the specific function and mechanism of the lncRNA NEAT1 in the progression of cardiac fibrosis to heart failure. In the present study, we have demonstrated that the lncRNA NEAT1 is upregulated in patients with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…EZH2 is the catalytic subunit of Polycomb Repressive Complex 2 (PRC2) and functions as a methyltransferase to mediate H3K27 trimethylation in the promoter region of target genes [ 45 , 46 ]. It reported that several lncRNAs could interact with EZH2 to epigenetically suppress the expression of the downstream gene [ 47 49 ]. For instance, CASC9 promoted esophageal squamous cell carcinoma (ESCC) progression by negatively regulating PDCD4 expression through recruiting EZH2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is the catalytic subunit of Polycomb Repressive Complex 2 (PRC2) and functions as a methyltransferase to mediate H3K27 trimethylation in the promoter region of target genes [ 45 , 46 ]. It reported that several lncRNAs could interact with EZH2 to epigenetically suppress the expression of the downstream gene [ 47 49 ]. For instance, CASC9 promoted esophageal squamous cell carcinoma (ESCC) progression by negatively regulating PDCD4 expression through recruiting EZH2 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 has been previously associated with matrix remodeling, but with contradictory results depending on the analysis method used. Several studies associated NEAT1 overexpression with fibrosis progression and also with fibrosis reduction [ 65 , 66 , 67 , 68 ]. Nevertheless, studies of matrix remodeling did not analyze NEAT1 at the isoform level.…”
Section: Resultsmentioning
confidence: 99%
“…lncRNA-ANRIL alters the expression of fibronectin (FN), type IV collagen (Col1α4), and VEGF by interacting with multiple epigenetic regulators, including EZH2, p300, and regulates cardiac fibrosis in diabetic mice [ 107 ]. Furthermore, LncRNA NEAT1 inhibits Smad7 expression by recruiting EZH2 to the Smad7 promoter region, which ultimately aggravates the progression of cardiac fibrosis, while silencing NEAT1 significantly ameliorates TAC surgery-induced cardiac fibrosis and dysfunction in mice [ 108 ]. Moreover, in spontaneously hypertensive rats (SHRs), SUV39H1 is recruited by lncRNA MALAT1, resulting in H3K9me3 of MyoD-binding loci to mediate cardiac fibrosis [ 110 ].…”
Section: Histone Modification In Cfs Activation and Cardiac Fibrosismentioning
confidence: 99%